Mejoramiento de la calidad de atención de enfermería en los pacientes que acuden al Hospital Básico San Gabriel 2019 - Chapí Patiño, Daniela Elizabeth (2019)
The present research study was carried out al the Basic Hospital San Gabriel in the Carchi province and it was aimed at implementing educational strategies to improve the quality of nursing care in patients treated here. By doing this research, it was possible to analyze some bibliography related to the theoretical framework where topics such as attention quality were deeply studied. In addition, the research methodology used was the descriptive study, which allowed the analysis of the problem, and the survey was used as the ideal technique with a sample of 100% of the population. The main results show that the communication, user satisfaction and attention quality are not appropriate enough. Therefore, a proposal is presented in order to improve this problem by using educational strategies based on diagnosis, aimed at the staff to improve the attention quality. It was possible to make the entire population aware of providing good communication, this is evidenced by the application of a post survey whose results were positive in 95.24%. In conclusion, with the obtained results there is evidence of an acceptable degree of satisfaction that they receive from this Institution, the continuous improvement of quality is not only based on the infrastructure or products that the Hospital has but also on the adequaoy of these to the needs of the user, thatis, the appropriate treatment and waiting time to fully satisty the user's perspectives.